Biodiversitätsmuseum Göttingen The storyline English edition - Bleidorn, Christoph; Aguado Molina, Maria Teresa (Universitätsverlag Göttingen, 2021)
Currently, researchers from many excellent departments are working in the broad field of biodiversity and sustainability research on the Göttingen Campus. In the Museum of Biodiversity, we will introduce the research from these groups to present what biodiversity is, how it evolved and its interactions within ecosystems. We, as humans, totally depend on this biodiversity and are part of it. However, because of our impact, biodiversity is in crisis. We will show the significant impact of human activity on the planet's biodiversity. Understanding that biodiversity matters to us and what that means for our future is the key to start acting to stop this crisis. The planned exhibition will opened in will be hosted at the second floor of the former Naturhistorisches Museum building at the Berliner Straße. The overall aim of the museum is to promote and support a scientific culture in the society. By kindling enthusiasm for the natural world and its exploration, we strive to make science from the university accessible to the general public.